2021
DOI: 10.3389/fneur.2021.667055
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Function After Cochlear Implantation in Partial Deafness Treatment

Abstract: Introduction: Cochlear implantation is a fully accepted method of treating individuals with profound hearing loss. Since the indications for cochlear implantation have broadened and include patients with low-frequency residual hearing, single-sided deafness, or an already implanted ear (meaning bilateral cochlear implantation), the emphasis now needs to be on vestibular protection.Materials and Methods: The research group was made up of 107 patients operated on in the otorhinolaryngosurgery department: 59 fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
0
8
1
Order By: Relevance
“…Although the subjects’ biases were inevitable among different intervals, the results had definite meanings. In this report, at 1 and 3 months post-CI, the percent fail rates of cVEMP and oVEMP were higher than those of a recent report that showed that 19.2% of patients in cVEMP and 17.4% in oVEMP had post-operative function loss at 1–3 months after HP surgery ( Sosna-Duranowska et al, 2021 ). Regarding the vHIT results 4–6 months post-operatively, a similar difference was observed.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…Although the subjects’ biases were inevitable among different intervals, the results had definite meanings. In this report, at 1 and 3 months post-CI, the percent fail rates of cVEMP and oVEMP were higher than those of a recent report that showed that 19.2% of patients in cVEMP and 17.4% in oVEMP had post-operative function loss at 1–3 months after HP surgery ( Sosna-Duranowska et al, 2021 ). Regarding the vHIT results 4–6 months post-operatively, a similar difference was observed.…”
Section: Discussioncontrasting
confidence: 73%
“…Although 23.61% of our patients used counter electrodes and four recipients implanted with the Nurotron CS-10A electrode, other protective techniques were used. Only one or two evaluation time points were analyzed in a few previous studies on vestibular function protection with soft surgery ( Guan et al, 2021 ; Sosna-Duranowska et al, 2021 ; Tsukada and Usami, 2021 ). The variation in vestibular function at different follow-ups during the first year was analyzed in this study for the first time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For patients who suffer from hearing loss after an episode of SSNHL, cochlear implantation may be the only opportunity, due to the possible ossification of the cochlea-especially after viral infections [20][21][22][23]. As far as diagnostics of moderate to profound sensorineural hearing loss (MPSHL), the use of cVEMPs (cervical vestibular-evoked myogenic potentials) to identify and intervene promptly in cases of vestibular disorders, which could endanger the process of integration of the critical sensory stimuli for correct posture and locomotion [24,25]. Additionally, the evidence for viral involvement in SSNHL, Ménière's disease, and vestibular neuritis is indirect and equivocal [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is no definite conclusion on the time of vestibular function evaluation after cochlear implantation. In some studies on vestibular function changes after cochlear implantation, the time of vestibular function evaluation varies from 1 month to 12 months after surgery ( 18 , 94 96 ). Long-term follow-up is available to observe the long-term effects of cochlear implantation on vestibular function in children.…”
Section: Recommended Strategiesmentioning
confidence: 99%